Signal and Information Processing, Networking and Computers Proceedings of the 9th International Conference on Signal and Information Processing, Networking and Computers (ICSINC) - Sun, Songlin; Hong, Tao.; Yu, Peng.; Zou, Jiaqi (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book collects selected papers from the 9th Conference on Signal and Information Processing, Networking and Computers held online, in December, 2021. The book focuses on the current works of information theory, communication system, computer science, aerospace technologies, big data and other related technologies. Readers from both academia and industry of this field can contribute and find their interests from the book.
Wireless Communication System -- Algorithms Optimization and Implementation -- Video Coding and Communication.
Keywords: Telecommunication; Signal processing; Aerospace engineering; Astronautics; Communications Engineering, Networks; Signal, Speech and Image Processing .; Aerospace Technology and Astronautics